2009
DOI: 10.1111/j.1744-7402.2009.02374.x
|View full text |Cite
|
Sign up to set email alerts
|

Tribology–Structure Relationships in Silicon Oxycarbide Thin Films

Abstract: Silicon oxycarbide is a versatile material system that is attractive for many applications because of its ability to tune properties such as chemical compatibility, refractive index, electrical conductivity, and optical band gap through changes in composition. One particularly intriguing application lies in the production of biocompatible coatings with good mechanical properties. In this paper, we report on the wide range of mechanical and tribological property values exhibited by silicon oxycarbide thin films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…As shown in Fig. 6 , the Young’s modulus of SiCO increase with an increased carbon content, as reported by nanoindentation test 29 . Within different compositions, it ranges from 99 GPa to 120 GPa, which is within the scope of 90–110 GPa in experiments 5 30 .…”
Section: Resultssupporting
confidence: 75%
“…As shown in Fig. 6 , the Young’s modulus of SiCO increase with an increased carbon content, as reported by nanoindentation test 29 . Within different compositions, it ranges from 99 GPa to 120 GPa, which is within the scope of 90–110 GPa in experiments 5 30 .…”
Section: Resultssupporting
confidence: 75%
“…(a), its friction force is the lowest. Tribological interactions are known to be extremely complex, depending on roughness, tribochemical reactions, and structural rearrangement, all of which have great effects on the tribological properties . In this experiment, all of the samples were measured under constant surrounding temperature and humidity, using a certain AFM tip; therefore, no structural rearrangement was expected to occur, and the tribochemical reactions were supposed to be similar for all the films, as the amounts of atoms which compose the films are very much the same.…”
Section: Resultsmentioning
confidence: 99%
“…9 C and D. Over a range of penetration depths, the mean values of the reduced Young's modulus and hardness are found to be 106±6 and 12±1 GPa, respectively. An earlier study showed that SiOC ceramics with lower O/C ratios behave similarly to amorphous-SiC materials, while the mechanical properties of SiOC with higher O/C ratio are similar to those in amorphous SiO2 [37]. In the present work, the hardness and elastic modulus of AM fabricated SiOC materials lie between the predicted limit of amorphous SiO2 [37] and amorphous SiC [38] and are further in good agreement with reported values for silicon oxycarbide glasses with variable C/O ratio [37,39].…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…An earlier study showed that SiOC ceramics with lower O/C ratios behave similarly to amorphous-SiC materials, while the mechanical properties of SiOC with higher O/C ratio are similar to those in amorphous SiO2 [37]. In the present work, the hardness and elastic modulus of AM fabricated SiOC materials lie between the predicted limit of amorphous SiO2 [37] and amorphous SiC [38] and are further in good agreement with reported values for silicon oxycarbide glasses with variable C/O ratio [37,39]. It is worth emphasizing that our fabrication method resulted in SiOC ceramics with comparable or even slightly better mechanical properties than those of SiOC glasses fabricated either via hot-pressing or via radio frequency (RF)-magnetron sputtering.…”
Section: Mechanical Propertiesmentioning
confidence: 97%